THE METHODS OF SENIOR PUPILS TEACHING FOR MODELLING OF STEREOMETRIC FIGURES APPLYING INFORMATION AND COMMUNICATION TECHNOLOGIES - Inna O. Gulivata (Інформаційні технології і засоби навчання, 2013)
The topicality of the article is determined by the use of effective methods of visualization of geometric material aimed at teaching the pupils to build stereometrical figures and development of their spatial imagination. The proposed methods of senior pupils teaching how to build the fundamental stereometric figures with the application of information and communication technologies (ITC) are based on demonstrating computer models (DCM) of the objects under consideration and enable to optimize the organization of the study process and promote the development of pupils’ spatial imagination, taking into account their personal characteristics of development and the principles of differentiated teaching.